Irritable Bowel Syndrome in Saudi Adult Patient in King Khalid Hospital - Ahmed Anis Abdullah, Ibrahim Awad Mahdi Alyami, Muayyad Abdullah Abualjadayel,; Sarah Jemal AL-Qahtani, Sundus Anis Abdullah, Abdulghaffar Talal Halawani,; Ali Ghanem Ali Al Masad, Saleh Abdullah Alharbi, Tariq Ali Asery, Yaser Ali Asery,; Tahani Jathab Alshaibani, Esra Saleh Alamri, (International Journal of Innovative Research in Medical Science, 2017)
Irritable bowel syndrome (IBS) is one of the most common syndromes seen by gastroenterologists and primary care providers. The purpose of the present study was to review records of Saudi adult patients who suffer from irritable bowel syndrome in King Khalid hospital, and to identify relationship between The Irritable bowel syndrome and age, gender, eating habits, psychological problems and education and family history. for my study research the Irritable bowel syndrome more conman in adult male more than adult female .there is no relationship between the Irritable bowel syndrome and family history. The Irritable bowel syndrome is not associated with psychological problems. The most common presentation abdominal pain (87.5%), bloating (81.2%), and diarrhea (56.2%). All Patients have problems with eating habits, and they need to education.